The psychopathologies of cognitive capitalism : Part One - De Boever, Arne; Neidich, Warren; Beller, Jonathan; Berardi, Franco (Berlin : Archive Books, 2013)
Essays by Jonathan Beller ; Franco 'Bifo' Berardi ; Arne De Boever ; Jodi Dean ; Warren Neidich ; Patricia Pisters ; Jason Smith ; Tiziana Terranova ; Bruce Wexler
Published on the occasion of "The Psychopathologies of Cognitive Capitalism: Part Two" at ICI Berlin, this book collects the papers that were presented during the first part of the conference Los Angeles in November 2012.
boek
Keywords: Neidich, Warren